EFEK PROTEKSI EKSTRAK AIR PANAS BUAH MAHKOTA DEWA Phaleria macrocarpa (SCHEFF.) BOERL. TERHADAP STRES OKSIDASI AKIBAT FERRI SITRAT PADA KHAMIR Candida tropicalis - Heddy Julistiono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Yeast Candida tropiclis had been used as a cell model to investigate effects of drugs on cell level. Phaleria macrocarpa (Scheff.) Boerl., is traditionally used in Indonesia as medicinal plant. This study was to evaluate the antioxidant property of P. macrocarpa in cell level by using yeast C. tropicalis induced with ferric citrate. Ferric citrate of 1 mM or 5 mM induced oxidative stress in the the yeast, marked with increasing of an oxidative damage marker, malon dialdehyde (MDA). Concentration of 5 mM of Ferric citrate caused cell mortality but concentration of 1 mM did not affect cell viability. Hot water extract of P. macrocarpa of 1 mg/ml attenuated MDA level in yeast cell induced with 1 mM ferric citrate. Whereas, 1 mg/ml of P. macrocarpa decreased cell mortality of the yeast induced with 5 mM ferric citrate without decreasing level of MDA. However, 4 mg/ml of P. macrocarpa induced oxidative damage in yeast cell. The data may indicate the potential use of Indonesian traditional plant P. macrocarpa as herbal medicine for protecting human cell from oxidation damage.